The Paris apartment : a novel - Foley, Lucy (Novelist) (New York, NY : Harper Large Print, an imprint of HarperCollinsPublishers, 2022)
Arriving in Paris to stay with her brother Ben, Jess learns that he has gone missing, and to find him, starts digging into his life, realizing even though she has come to the City of Lights to escape her past, it's his future hanging in the balance.
Keywords: Brothers -- Fiction; Missing persons -- Fiction; Apartment houses -- Fiction; Paris (France) -- Fiction; Detective and mystery fiction; Psychological fiction; Thrillers (Fiction); Large type books